COMORBIDITIES IN LOW AND MEDIUM INCOME COUNTRIES OF CHILD MALNUTRITION: A SYSTEMATIC REVIEW - Arys Paramerta, Ni Putu Gladys (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Malnutrition or malnourishment is a condition that results from eating a diet in which nutrients are either not enough or are too much such that the diet causes health problems. Not enough nutrition is called undernutrition or undernourishment while too much is called over nutrition. According to the World Health Organization (WHO), malnutrition essentially means “bad nourishment” and can refer to the quantity as well as the quality of food eaten. The aim: This study aims to show the comorbidities in low and medium income countries of child malnutrition. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 576 articles, whereas the results of our search on SagePub brought up 130 articles. The results of the search conducted for the last year of 2013 yielded a total 361 articles for PubMed and 81 articles for SagePub. The result from title screening, a total 41 articles for PubMed and 20 articles for SagePub. In the end, we compiled a total of 10 papers. We included five research that met the criteria. Conclusion: Childhood nutrition is an integral component of a multifocal relationship with health, economic, social developments, and political system of the country. Child malnutrition under the age of 5 years has a great influence on the cultural, social, economic and community food practices.